Preparation methods and applications of Pd-C3N4 nanosheet catalytic materials
Patent Information
- Application Number
- CN202611226753.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-09
AI Technical Summary
所以目前的加氢改性催化剂具有分离困难,加氢部位局限性的缺点
[0023]本发明制备的Pd-C3N4纳米片催化材料加氢活性高,通过剥离程度的控制,调控催化材料的形貌,有利于大分子扩散,并通过载体与活性组分的电子转移调控,提高催化活性。实际运用中可以通过反应条件的优化实现SBS的选择加氢以及完全氢化。同时本发明加氢工艺简单,催化剂制备及反应中涉及的溶剂可循环利用,降低了环境污染和资源消耗。
Smart Images

Figure CN122875273A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of unsaturated polymer hydrogenation modification technology, specifically relating to a method for preparing and applying Pd-C3N4 nanosheet catalytic materials. Background Technology
[0002] SBS is a thermoplastic elastomer composed of styrene and butadiene segments. Due to the presence of unsaturated C=C and benzene rings in the polymer chain, its heat resistance, oxidation resistance, and UV resistance are poor, and it is often used in low-end manufacturing. Partially hydrogenated SBS (SEBS), obtained by hydrogenating the butadiene segment of SBS, has better thermal stability and oxidation resistance, improving the material's performance. Cyclic block copolymers (CBCs), the product of fully hydrogenating the butadiene and styrene segments of SBS, have even better thermal stability, transparency, UV resistance, and oxidation resistance, and are being extended to high-end fields such as medical devices, smart wearables, automotive parts, and protective materials. Hydrogenation modification of SBS not only improves the durability and industrial value of the material but also alleviates the overcapacity of basic rubber production, and the extension of production lines also improves the economic benefits of the products.
[0003] Currently, the main hydrogenation catalysts for the butadiene segment in SBS are homogeneous catalysts, such as the Ziegler-Natta type catalyst mentioned in patent CN115608420A and the metallocene catalyst described in patent CN111019051A. These catalysts have high hydrogenation activity for the C=C segment in the polymer. However, the difficulty in separating homogeneous catalysts leads to catalyst residue, which affects the performance of the product. Moreover, these catalysts only have hydrogenation activity for C=C and very low hydrogenation activity for the benzene ring segment, which limits the process of SBS hydrogenation modification.
[0004] Current heterogeneous hydrogenation catalysts mainly include noble metals such as Pd, Pt, and Rh supported on oxide supports such as CaCO3, BaSO4, and SiO2, as well as carbon materials such as activated carbon and carbon nanotubes. For example, patent CN117920200A uses Pd supported on graphene for the hydrogenation modification of polystyrene, and patent CN113908832A uses Pd supported on TiO2 for the hydrogenation modification of polystyrene. Some catalysts have harsh reaction conditions and limitations for the hydrogenation modification of unsaturated polymers, targeting only the C=C segment or benzene ring segment of the unsaturated polymer. Therefore, current hydrogenation modification catalysts suffer from difficulties in separation and limited hydrogenation sites. Summary of the Invention
[0005] To overcome the technical problems mentioned in the background art, this invention provides a Pd-C3N4 nanosheet catalytic material. This catalytic material is simple to prepare, low in cost, and has a sheet-like structure that facilitates macromolecular diffusion. The presence of edge nitrogen promotes electron transfer between the support and the active component, thereby improving catalytic activity. Furthermore, this catalytic material exhibits high hydrogenation activity in the SBS hydrogenation process, and by adjusting the hydrogenation process, partial and complete hydrogenation of SBS can be achieved. SBS products can be selectively hydrogenated to modify them according to application requirements, saving production costs and improving hydrogenation efficiency, thus possessing significant practical application value.
[0006] To achieve this goal, the technical solution adopted in this invention is as follows: the Pd-C3N4 nanosheet catalytic material for SBS hydrogenation comprises an active component Pd and a supported heterogeneous catalytic material with C3N4 nanosheets as the carrier. The material exhibits a sheet-like structure with a porous surface; the specific surface area of the Pd-C3N4 nanosheet catalytic material is 80~180 m². 2 / g, pore size 10~30 nm, pore volume 0.2~0.6 cm³ / g.
[0007] Furthermore, the C3N4 nanosheet catalytic support is prepared by exfoliating bulk C3N4. The exfoliated C3N4 nanosheets have a larger specific surface area and porosity, which is conducive to the diffusion of macromolecules. The more edge nitrogen is conducive to promoting electron transfer between the support and the active component, thereby improving catalytic activity.
[0008] The specific preparation method of the catalyst includes the following steps:
[0009] Step S1. A certain mass of C3N4 carrier precursor is placed in a tube furnace and heated to pyrolyze under N2 atmosphere;
[0010] The catalyst support precursor is selected from any one of urea, melamine or dicyandiamide, with melamine being preferred as the precursor.
[0011] The pyrolysis process involves heating the temperature to 500-550℃ at a rate of 5-10℃ / min and holding it for 3-5 hours.
[0012] Step S2. After the precursor is pyrolyzed, take it out, grind and sieve it, add protonating reagent solution and stir thoroughly for 1-2 hours, then sonicate for 1-2 hours, wash with deionized water until neutral, dry overnight at 60-80℃, and then place it in a tube furnace for thermal stripping treatment.
[0013] The support obtained by high-temperature pyrolysis is treated with a protonating agent, such as HCl, HNO3 or H2SO4, and then subjected to high-temperature thermal exfoliation to form C3N4 nanosheets with a sheet-like microstructure. The acid solution concentration is 1-10M, with HCl being the preferred protonating agent.
[0014] Thermal stripping involves heating the temperature to 500-550℃ at a rate of 4-6℃ / min and holding it for 3-5 hours.
[0015] Step S3. Weigh a certain amount of Pd precursor solution and add it to the exfoliated C3N4 nanosheets. After sonication for 30 min, soak for 2 h. After completion, dry at 60-80 ℃ and place in a tube furnace under H2 atmosphere. Heat to 300-350 ℃ and maintain for 2-4 h to reduce to obtain the reduced Pd-C3N4 nanosheet catalytic material.
[0016] The precursor of the active component Pd can be any one or more of palladium chloride, palladium acetate or palladium nitrate, with palladium chloride being preferred as the palladium source; the H2 flow rate is 50-100 mL / min, and the heating rate is 2-3℃ / min.
[0017] Pd-C3N4 nanosheet catalysts can be modified by adjusting the reaction process to achieve hydrogenation of the C=C segment in SBS and hydrogenation of both the C=C segment and the benzene ring segment in SBS. The process is simple, the solvent can be recycled and reused, which is in line with the concept of green chemistry.
[0018] The catalyst is used for the hydrogenation modification of SBS. The specific method is to place the raw material SBS, the reaction solvent cyclohexane and the catalyst in a reaction vessel, and react at a temperature of 150-210 ℃ and a pressure of 6-8 MPa for 6-12 h. After cooling, a hydrogenation solution is obtained.
[0019] Furthermore, the catalyst material and filtrate are separated by filtration, and the filtrate is rotary evaporated to remove the solvent cyclohexane, yielding the hydrogenation product, which is then dried in an oven.
[0020] The degree of hydrogenation of the C=C segment in the hydrogenation product was determined by bromoiodine titration; the degree of hydrogenation of the benzene ring segment in the hydrogenation product was determined by ultraviolet spectrophotometry at 261.5 nm.
[0021] Furthermore, reacting at 170 °C and 6 MPa for 6 h can efficiently and selectively hydrogenate the C=C segment of SBS; reacting at 190 °C and 6 MPa for 10 h can achieve efficient full hydrogenation of both the C=C segment and the benzene ring segment of SBS.
[0022] In summary, the present invention has the following beneficial effects:
[0023] The Pd-C3N4 nanosheet catalytic material prepared by this invention exhibits high hydrogenation activity. By controlling the degree of exfoliation, the morphology of the catalytic material can be modulated, which is beneficial for macromolecular diffusion. Furthermore, the catalytic activity is enhanced through electron transfer regulation between the support and the active component. In practical applications, selective hydrogenation and complete hydrogenation of SBS can be achieved through optimization of reaction conditions. Simultaneously, the hydrogenation process of this invention is simple, and the solvents involved in catalyst preparation and the reaction can be recycled, reducing environmental pollution and resource consumption. Attached Figure Description
[0024] Figure 1 XRD patterns of the catalysts in Example 1 and Examples 1, 2, and 4 are shown for comparison.
[0025] Figure 2 SEM images of the catalyst materials prepared in Comparative Examples 1(a) and 1(b).
[0026] Figure 3 XPS images of the catalyst materials in Example 1 and Example 1 are shown for comparison, where a represents N 1s orbitals and b represents Pd 3d orbitals. Detailed Implementation
[0027] To further illustrate the present invention and the technical means and effects adopted to achieve the intended purpose, a method for preparing Pd-C3N4 nanosheet catalytic materials according to the present invention is provided. This catalytic material can be used in the SBS hydrogenation modification process and has high activity and versatility. The specific implementation methods, features, and effects are described in detail. However, the present invention is not limited to the following specific embodiments. Those skilled in the art can implement the present invention using various other specific embodiments based on the disclosed content. Any simple changes or modifications to the design structure and concept of the present invention fall within the protection scope of the present invention. It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other.
[0028] Comparative Example 1
[0029] S1. First, weigh 10g of melamine powder and place it in a tube furnace. Under a N2 atmosphere, heat the furnace to 550℃ at a heating rate of 5℃ / min and maintain the temperature for 4 hours. After calcination, cool the furnace and remove the powder to obtain blocky C3N4. Grind the blocky C3N4 and pass it through a 40-mesh sieve for later use. BET testing showed that the specific surface area of the C3N4 carrier was 79.3 m². 2 / g, pore volume 0.19 cm³ 3 / g, with an average pore size of 9.8 nm.
[0030] S2. Take 1 g of ground and sieved C3N4, prepare 1 g of PdCl2 into 100 mL of aqueous solution, add 8.33 mL of PdCl2 solution to C3N4, sonicate for 30 min and impregnate for 2 h, place in an oven to dry, and obtain Pd-C3N4 catalyst loaded with 5% Pd.
[0031] Example 1
[0032] S1. Weigh 10g of melamine powder, put it into a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min under N2 atmosphere, and maintain it for 4h. After pyrolysis, cool it down and take it out to obtain blocky C3N4, grind it through a 40-mesh sieve for later use.
[0033] S2. Take 2 g of ground and sieved powder, add 50 mL of 10 M HCl, stir at 200 r / min for 1 h, sonicate for 1 h, wash with deionized water until neutral, filter, dry, and place in a tube furnace. Under N2 atmosphere, heat to 520 ℃ at a heating rate of 4 ℃ / min and maintain for 3 h. After thermal exfoliation, cool and remove to obtain C3N4 nanosheets, grind and pass through a 40 mesh sieve for later use. Physical adsorption-desorption (BET) test shows that the specific surface area of C3N4 nanosheets is 168.1 m². 2 / g, pore volume 0.56 cm³ 3 / g, with an average pore size of 23.2 nm;
[0034] S3. Take 1 g of ground and sieved C3N4 nanosheets, prepare 1 g of PdCl2 into 100 mL of aqueous solution, add 8.33 mL of PdCl2 solution to C3N4 nanosheets, sonicate for 30 min and impregnate for 2 h, and dry in an oven at 60℃ to obtain Pd-C3N4 nanosheet catalyst loaded with 5% Pd.
[0035] Example 2
[0036] S1. Weigh 10g of melamine powder, put it into a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min under N2 atmosphere, and maintain it for 4h. After pyrolysis, cool it down and take it out to obtain blocky C3N4, grind it through a 40-mesh sieve for later use.
[0037] S2. Take 2 g of ground and sieved powder, add 50 mL of 1 M HCl, stir at 200 r / min for 1 h, sonicate for 1 h, wash with deionized water until neutral, filter, dry, and place in a tube furnace. Under N2 atmosphere, heat to 520 ℃ at a heating rate of 4 ℃ / min and maintain for 3 h. After thermal exfoliation, cool and remove to obtain C3N4 nanosheets, grind and pass through a 40 mesh sieve for later use. BET test shows that the specific surface area of C3N4 nanosheets is 94.5 m².2 / g, pore volume 0.28 cm³ 3 / g, with an average pore size of 11.7 nm;
[0038] S3. Take 1 g of ground and sieved C3N4 nanosheets, prepare 1 g of PdCl2 into 100 mL of solution, add 8.33 mL of PdCl2 solution to C3N4 nanosheets, sonicate for 30 min and impregnate for 2 h, and dry in an oven at 60℃ to obtain Pd-C3N4 nanosheet catalyst loaded with 5% Pd.
[0039] Example 3
[0040] S1. Weigh 10g of melamine powder, put it into a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min under N2 atmosphere, and maintain it for 4h. After pyrolysis, cool it down and take it out to obtain blocky C3N4, grind it through a 40-mesh sieve for later use.
[0041] S2. Take 2 g of ground and sieved powder, add 50 mL of 3 M HCl, stir at 200 r / min for 1 h, sonicate for 1 h, wash with deionized water until neutral, filter, dry, and place in a tube furnace. Under N2 atmosphere, heat to 520 ℃ at a heating rate of 4 ℃ / min and maintain for 3 h. After thermal exfoliation, cool and remove to obtain C3N4 nanosheets, grind and pass through a 40 mesh sieve for later use. BET test shows that the specific surface area of C3N4 nanosheets is 107.6 m². 2 / g, pore volume 0.32 cm³ 3 / g, with an average pore size of 12.4 nm;
[0042] S3. Take 1 g of ground and sieved C3N4 nanosheets, prepare 1 g of PdCl2 into 100 mL of solution, add 8.33 mL of PdCl2 solution to C3N4 nanosheets, sonicate for 30 min and impregnate for 2 h, and dry in an oven at 60℃ to obtain Pd-C3N4 nanosheet catalyst loaded with 5% Pd.
[0043] Example 4
[0044] S1. Weigh 10 g of melamine powder, put it into a tube furnace, heat it to 550 ℃ at a heating rate of 5 ℃ / min under N2 atmosphere, and maintain it for 4 h. After pyrolysis, cool it down and take it out to obtain blocky C3N4, grind it through a 40 mesh sieve for later use.
[0045] S2. Take 2 g of ground and sieved powder, add 50 mL of 5 M HCl, stir at 200 r / min for 1 h, sonicate for 1 h, wash with deionized water until neutral, filter, dry, and place in a tube furnace. Under N2 atmosphere, heat to 520 ℃ at a heating rate of 4 ℃ / min and maintain for 3 h. After thermal exfoliation, cool and remove to obtain C3N4 nanosheets, grind and pass through a 40 mesh sieve for later use. BET test shows that the specific surface area of C3N4 nanosheets is 127.1 m². 2 / g, pore volume 0.47 cm³ 3 / g, with an average pore size of 15.5 nm;
[0046] S3. Take 1 g of ground and sieved C3N4 nanosheets, prepare 1 g of PdCl2 into 100 mL of solution, add 8.33 mL of PdCl2 solution to C3N4 nanosheets, sonicate for 30 min and impregnate for 2 h, and dry in an oven at 60℃ to obtain Pd-C3N4 nanosheet catalyst loaded with 5% Pd.
[0047] Example 5
[0048] S1. Weigh 10g of melamine powder, put it into a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min under N2 atmosphere, and maintain it for 4h. After pyrolysis, cool it down and take it out to obtain blocky C3N4, grind it through a 40-mesh sieve for later use.
[0049] S2. Take 2 g of ground and sieved powder, add 50 mL of 7 M HCl, stir at 200 r / min for 1 h, sonicate for 1 h, wash with deionized water until neutral, filter, dry, and place in a tube furnace. Under N2 atmosphere, heat to 520 ℃ at a heating rate of 4 ℃ / min and maintain for 3 h. After thermal exfoliation, cool and remove to obtain C3N4 nanosheets, grind and pass through a 40 mesh sieve for later use. BET test shows that the specific surface area of C3N4 nanosheets is 153.2 m². 2 / g, pore volume 0.51 cm³ 3 / g, with an average pore size of 18.1nm;
[0050] S3. Take 1 g of ground and sieved C3N4 nanosheets, prepare 1 g of PdCl2 into 100 mL of solution, add 8.33 mL of PdCl2 solution to C3N4 nanosheets, sonicate for 30 min and impregnate for 2 h, and dry in an oven at 60℃ to obtain Pd-C3N4 nanosheet catalyst loaded with 5% Pd.
[0051] Example 6
[0052] S1. First, weigh 20g of urea powder and place it in a tube furnace. Under a N2 atmosphere, heat the furnace to 550℃ at a heating rate of 5℃ / min and maintain the temperature for 4 hours. After pyrolysis, cool the furnace and remove the powder to obtain C3N4. Grind the C3N4 powder through a 40-mesh sieve for later use. BET testing showed that the specific surface area of the C3N4 carrier was 81.7 m². 2 / g, pore volume 0.24 cm³ 3 / g, with an average pore size of 7.6 nm;
[0053] S2. Take 0.5 g of the ground and sieved powder, add 25 mL of 10 M HCl, stir at 200 r / min for 1 h, sonicate for 1 h, wash with deionized water until neutral, filter, dry, and place in a tube furnace. Under N2 atmosphere, heat to 520 ℃ at a heating rate of 4 ℃ / min and maintain for 3 h. After thermal exfoliation, cool and remove to obtain C3N4 nanosheets, grind and pass through a 40 mesh sieve for later use. BET test shows that the specific surface area of the C3N4 nanosheets is 172.3 m². 2 / g, pore volume 0.34 cm³ 3 / g, with an average pore size of 14.3 nm;
[0054] S2. Take 0.5 g of ground and sieved C3N4, prepare 1 g of PdCl2 into 100 mL of solution, add 4.17 mL of PdCl2 solution to C3N4, sonicate for 30 min and impregnate for 2 h, and dry in an oven at 60℃ to obtain Pd-C3N4 catalyst loaded with 5% Pd.
[0055] Example 7
[0056] S1. Weigh 10g of melamine powder, put it into a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min under N2 atmosphere, and maintain it for 4h. After pyrolysis, cool it down and take it out to obtain blocky C3N4, grind it through a 40-mesh sieve for later use.
[0057] S2. Take 2 g of ground and sieved powder, add 50 mL of 1 M HNO3, stir at 200 r / min for 1 h, sonicate for 1 h, wash with deionized water until neutral, filter, dry, and place in a tube furnace. Under N2 atmosphere, heat to 520 ℃ at a heating rate of 4 ℃ / min and maintain for 3 h. After thermal exfoliation, cool and remove to obtain C3N4 nanosheets, grind and pass through a 40 mesh sieve for later use. Physical adsorption-desorption (BET) test shows that the specific surface area of C3N4 nanosheets is 178.3 m². 2 / g, pore volume is 0.41 cm³ 3 / g, with an average pore size of 24.9 nm;
[0058] S3. Take 1 g of ground and sieved C3N4 nanosheets, prepare 1 g of PdCl2 into 100 mL of solution, add 8.33 mL of PdCl2 solution to C3N4 nanosheets, sonicate for 30 min and impregnate for 2 h, place in an oven to dry, and obtain Pd-C3N4 nanosheet catalyst loaded with 5% Pd.
[0059] Example 8
[0060] S1. Weigh 10g of melamine powder, put it into a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min under N2 atmosphere, and maintain it for 4h. After pyrolysis, cool it down and take it out to obtain blocky C3N4, grind it through a 40-mesh sieve for later use.
[0061] S2. Take 2 g of ground and sieved powder, add 50 mL of 10 M HCl, stir at 200 r / min for 1 h, sonicate for 1 h, wash with deionized water until neutral, filter, dry, and place in a tube furnace. Under N2 atmosphere, heat to 550 ℃ at a heating rate of 4 ℃ / min and maintain for 3 h. After thermal exfoliation, cool and remove to obtain C3N4 nanosheets, grind and pass through a 40 mesh sieve for later use. BET test shows that the specific surface area of C3N4 nanosheets is 160.2 m². 2 / g, pore volume 0.57 cm³ 3 / g, with an average pore size of 24.5 nm;
[0062] S3. Take 1 g of ground and sieved C3N4 nanosheets, prepare 1 g of PdCl2 into 100 mL of solution, add 8.33 mL of PdCl2 solution to C3N4 nanosheets, sonicate for 30 min and impregnate for 2 h, and dry in an oven at 60℃ to obtain Pd-C3N4 nanosheet catalyst loaded with 5% Pd.
[0063] Example 9
[0064] S1. The catalyst support preparation process is the same as in Example 1.
[0065] S2. Take 1 g of ground and sieved C3N4 nanosheets, prepare 1 g of palladium acetate into 100 mL solution, add 11 mL of palladium acetate solution to C3N4 nanosheets, sonicate for 30 min and impregnate for 2 h, place in an oven to dry, and obtain Pd-C3N4 nanosheet catalyst loaded with 5% Pd.
[0066] The hydrogenation performance of the catalytic materials prepared in Examples 1-9 and Comparative Example 1 was evaluated. The prepared 5% Pd-C3N4 nanosheet catalytic material was placed in a tube furnace and heated to 350 °C at a heating rate of 2 °C / min under H2 atmosphere, and maintained for 2 h to obtain the reduced catalytic material.
[0067] 2g of SBS (grade 791, Baling Petrochemical) and 0.2g of Pd-C3N4 catalyst were weighed and placed in a 200 mL reactor. 100 mL of cyclohexane was added as a solvent. After sealing, N2 was introduced to replace the air in the reactor, followed by hydrogen gas. The temperature was raised to the reaction temperature, and hydrogen gas was added to the reaction pressure. After reacting for a period of time, the hydrogenation reaction was completed. After cooling, the pressure was released, and the solution in the reactor was removed. The solvent was collected by filtration and dried to obtain the hydrogenated product. The degree of hydrogenation of the C=C segment and the benzene ring segment in SBS was determined by bromine-iodine titration and ultraviolet fluorescence spectroscopy. The specific reaction conditions and hydrogenation effects of the catalyst prepared in the above examples are shown in the table below.
[0068] Table 1. Effect of protonation stripping on the hydrogenation performance of Pd-C3N4 catalyst
[0069] Comparative Example 1 210 8 10 100 56.1 Example 1 210 8 10 100 99.7 Example 2 210 8 10 100 93.4 Example 3 210 8 10 100 95.6 Example 4 210 8 10 100 97.5 Example 5 210 8 10 100 98.3
[0070] Table 2 BET characterization of catalysts in Examples 1-5
[0071] Comparative Example 1 79.3 0.19 9.8 Example 1 168.1 0.56 23.2 Example 2 94.5 0.28 11.7 Example 3 107.6 0.32 12.4 Example 4 127.1 0.47 15.5 Example 5 153.2 0.51 18.1
[0072] The hydrogenation activity was significantly improved after protonation treatment, and the activity gradually increased with increasing protonating reagent concentration. This is because the more thorough exfoliation resulted in nanosheets with a larger specific surface area and pore size, which facilitates the diffusion of macromolecular polymers and improves reaction efficiency. Figure 3 It can be seen that the stripped catalytic material has more pyridine N structures, which is more conducive to electron transfer with the active component Pd, resulting in a higher Pd content. 0 This improves hydrogenation activity.
[0073] Table 3. Effect of precursors on hydrogenation performance
[0074] Example 1 210 8 10 100 99.7 Example 6 210 8 10 100 84.6
[0075] Table 4. BET characterization of catalysts in Examples 1 and 6
[0076] Example 1 168.1 0.56 23.2 Example 6 172.3 0.34 14.3
[0077] Experiments with urea as a precursor revealed that the catalyst treated with the same protonating reagent had smaller pore volume and pore size, which limited the diffusion of macromolecules, resulting in a slightly lower hydrogenation effect than melamine.
[0078] Table 5. Effect of protonating reagent on hydrogenation performance
[0079] Example 1 210 8 10 100 99.7 Example 7 210 8 10 100 98.2
[0080] Table 6. BET characterization of catalysts in Examples 1 and 7
[0081] Example 1 168.1 0.56 23.2 Example 7 178.3 0.41 24.9
[0082] Experiments with nitric acid as a protonating agent revealed that, due to its stronger proton-donating ability, the resulting catalytic material also exhibited high hydrogenation activity.
[0083] Table 7. Effect of stripping temperature on hydrogenation performance
[0084] Example 1 210 8 10 100 99.7 Example 8 210 8 10 100 99.2
[0085] Table 8. BET characterization of catalysts in Examples 1 and 8
[0086] Example 1 168.1 0.56 23.2 Example 8 160.2 0.57 24.5
[0087] Attempts to increase the exfoliation temperature revealed a decrease in the specific surface area of the material. This may be due to excessively high temperatures causing condensation at some edge locations, resulting in a slight reduction in hydrogenation activity.
[0088] Table 9. Effect of Pd precursors on hydrogenation performance
[0089] Example 1 210 8 10 100 99.7 Example 9 210 8 10 100 98.9
[0090] The catalyst prepared using palladium acetate as a Pd precursor solution still exhibits high catalytic activity.
[0091] Table 10 Investigation of partial hydrogenation conditions in Example 1
[0092] Example 1 150 6 6 67.4 0 Example 1 160 6 6 80.4 3.4 Example 1 170 6 6 98.1 5.6 Example 1 180 6 10 100 36.4 Example 1 190 6 10 100 95.8 Example 1 210 8 10 100 99.7
[0093] The reaction conditions of the catalyst prepared in Example 1 were investigated and it was found that under mild reaction conditions, the catalyst can achieve selective hydrogenation of SBS, and under relatively high temperature and high pressure reaction conditions, it can achieve complete hydrogenation of SBS, demonstrating the versatility of the catalyst.
[0094] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been shown above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A method for preparing Pd-C3N4 nanosheet catalytic material, characterized in that, The preparation method steps are as follows: Step S1. Place the C3N4 carrier precursor in a tube furnace and heat it up for pyrolysis under a N2 atmosphere; Step S2. After the precursor is pyrolyzed, it is taken out, ground and sieved, a protonating reagent solution is added, and it is stirred and sonicated. Then it is washed with deionized water until neutral, dried, and placed in a tube furnace for thermal stripping treatment. Step S3. Weigh the Pd precursor solution and add it to the exfoliated C3N4 nanosheets. After impregnation, dry the nanosheets and place them in a tube furnace to reduce them under H2 atmosphere to obtain the reduced Pd-C3N4 nanosheet catalytic material.
2. The method for preparing Pd-C3N4 nanosheet catalytic material according to claim 1, characterized in that, In step S1, the C3N4 carrier precursor is selected from any one of urea, melamine or dicyandiamide. The pyrolysis is carried out in a muffle furnace by heating to 500-550℃ at a heating rate of 5-10℃ / min and holding for 3-5 hours.
3. The method for preparing Pd-C3N4 nanosheet catalytic material according to claim 1, characterized in that, In step S2, the protonating reagent is any one of HCl, HNO3, or H2SO4, and the acid solution concentration is 1-10 M.
4. The method for preparing Pd-C3N4 nanosheet catalytic material according to claim 1, characterized in that, After the precursor is pyrolyzed in step S2, it is taken out, ground and sieved, and then a protonating reagent solution is added and stirred thoroughly for 1-2 hours. After sonication for 1-2 hours, it is washed with deionized water until neutral.
5. The method for preparing Pd-C3N4 nanosheet catalytic material according to claim 1, characterized in that, In step S2, the thermal stripping is performed in a tube furnace under a N2 atmosphere, where the temperature is increased to 500-550℃ at a heating rate of 4-6℃ / min and held for 3-5 hours.
6. The method for preparing Pd-C3N4 nanosheet catalytic material according to claim 1, characterized in that, In step S3, the Pd precursor solution is prepared from any one of palladium chloride, palladium acetate or palladium nitrate. Pd is loaded onto the surface of the exfoliated C3N4 nanosheets using an equal-volume impregnation method and then dried at 60-80 °C.
7. The method for preparing Pd-C3N4 nanosheet catalytic material according to claim 1, characterized in that: In step S3, the H2 flow rate is 50-100 mL / min, and the temperature is increased to 300-350℃ at a heating rate of 2-3℃ / min, and maintained for 2-4 h for catalytic reduction.
8. A Pd-C3N4 nanosheet catalytic material prepared by the method according to any one of claims 1-7, characterized in that, The Pd-C3N4 nanosheet catalytic material comprises the active component Pd and the support C3N4 nanosheets, and the material exhibits a sheet-like structure.
9. The Pd-C3N4 nanosheet catalytic material according to claim 8, characterized in that, The Pd-C3N4 nanosheet catalytic material has a specific surface area of 80~180 m². 2 / g, pore size 10~30 nm, pore volume 0.2~0.6 cm³ / g.
10. An application of the Pd-C3N4 nanosheet catalytic material prepared by the method according to any one of claims 1-7, characterized in that, The Pd-C3N4 nanosheet catalytic material is used to catalyze the partial and complete hydrogenation of styrene-butadiene-styrene block copolymer (SBS).
Citation Information
Patent Citations
Preparation of oxygen vacancy regulated supported palladium-based catalyst and application of catalyst in hydrogenation of polystyrene
CN113908832A
Method for preparing poly (cyclohexyl ethylene) by catalyzing polystyrene hydrogenation and catalyst
CN117920200A